Stamps - Briggs, Michael (New York : Random House, 1993)
Provides information on the history of stamps and postal services and gives advice on identifying, handling, displaying, buying, and trading stamps.
Includes index.
Keywords: Stamp collecting -- Juvenile literature; Stamp collecting